A comparison of customer perceived service quality in discount versus traditional grocery stores: An examination of service quality measurement scales in a Swedish context. Issue 4 (17th November 2014) - Anselmsson, Johan; Johansson, Ulf
Abstract : Purpose: – The overall purpose of this study is to enhance the understanding of customer perceived service quality within grocery retailing in a North European context. We do this by comparing customer perceived service quality evaluations of the traditional supermarket store with evaluations of the discount store. Design/methodology/approach: – This study is based on empirical data from four store cases (two traditional and two discount stores), including information gained from a total of 542 respondents. In the study, we have used and tested a model of grocery store service quality, presented in Vázquez et al. (2001), with structural equation modelling (LISREL) and traditional multivariate analysis (SPSS). Findings: – The ability of the Vázquez et al. (2001) model to capture customer perceived quality was below 40 per cent for both concepts which signals limited relevance and that important dimensions in the service evaluation could be missing for both of the two concepts, at least in a North European context. The results show that the traditional supermarket outperforms the discount stores on all service aspects but availability and reliability. When comparing the determinants of the service quality evaluation, the two concepts are very similar. Finally, the overall results regarding determinants of service quality show resemblance to retail studies in other countries and cultures. Research limitations/implications: – This study has been limited to investigate service quality in Sweden and from two out of at least five possible retail concepts. As the explanatory power of the model is limited, future studies should explore other possible determinants of service quality, e.g. the role of technological innovations. Practical implications: – Kotler and Keller (2012) proposes five generic differentiation strategies: product, service, people, channels and image. The results suggest that traditional grocery stores that choose to differentiate and position themselves by focusing on service rather than physical product differentiation should work with assortment issues as well. In order to decide which aspect of service to choose and promote, companies should emphasise differences that are considered important by customers, distinct from competitors and superior in terms of delivering the overall benefit – in this case – in terms of service quality. The results show that the policy dimension would satisfy all three criterions. Social implications: – The study enhances the understanding of customer perceived service quality within grocery retailing, specifically in comparison between the supermarket and the discount store concept. Originality/value: – This study is the first to focus on whether there is a divergence in service quality and service quality measuring between the traditional supermarket concept and the growing discount concept, and if so to what extent. Furthermore, it is a test of a model that has gained acceptance in Latin and South European countries, but in the context of Northern Europe.